The Concept of equality and its urgency to accommodate Indonesia's diversity: A study of Bhikhu Parekh's perspective - Ramadhan, Idang; Eriranda, Afgha Okza (Proceeding International Conference on Religion, Science and Education, 2025)
This study examines the concept of equality according to Bhikhu Parekh and evaluates its urgency to accommodate diversity by connecting Parekh's theoretical thinking with the practical problems faced by Indonesia. Tensions between the majority and minority communities in Indonesia are shaped by varying degrees of cultural assimilation and loyalty to the nation. Majority groups are often favoured in shaping cultural norms, political power, and access to resources, which can impact equality. The peak of conflict between majority and minority communities in Indonesia often manifests in discrimination, violence, and social unrest. This research was conducted using a literature research method, which involved collecting data through the study and understanding of theories from various literature. The data comes from books, journals, previous research, and other relevant documents. Data was collected by searching and filtering literature on equality and diversity management and Bhikhu Parekh's thoughts. The collected data is then analyzed by compiling and connecting information to conclusions. Modern multicultural societies struggle to balance unity and diversity as differences deepen. Parekh believes that equality should be culturally contextual, not universal. Managing Indonesia's diversity needs to be done with dialogue and tolerance. Ensuring equality means providing inclusive, fair, and harmonious opportunities for all individuals and groups. This research is expected to offer practical solutions and new perspectives on how equality can be applied to overcome the diversity problem in Indonesia.